2016
DOI: 10.1590/18069657rbcs20140664
|View full text |Cite
|
Sign up to set email alerts
|

Soil Chemistry after Irrigation with Treated Wastewater in Semiarid Climate

Abstract: Soil irrigation using treated wastewater in the Brazilian semiarid region is a promising practice as this area currently faces water scarcity and pollution of water resources by domestic sewage. The aim of this study was to evaluate the use of treated wastewater in drip irrigation and its effect on the chemistry of soil cultivated with squash (Cucurbita maxima Duch.) Coroa IAC and to verify whether there was an increase in soil salinity under a semiarid climate. The experiment was conducted for 123 days on a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
0
12
2
1
Order By: Relevance
“…Similar result was found by Santos et al (2017) in successive maize, cotton, and common bean crops. SOM is usually altered by TTW after several years of use (XU et al, 2010); however, the use of high wastewater rates (150% of the maximum water demand) in semiarid regions can raise the SOM (OLIVEIRA et al, 2016). The results of the present study showed an increase in SOM when compared to that before the experiment implementation (Table 1), presenting averages of 20.8% (0.0-0.2 m layer) and 28.6% (0.2-0.4 m layer); this can be explained by the decomposition of plant residues, such as leaves and stems of banana trees in the experimental area.…”
Section: Resultsmentioning
confidence: 99%
“…Similar result was found by Santos et al (2017) in successive maize, cotton, and common bean crops. SOM is usually altered by TTW after several years of use (XU et al, 2010); however, the use of high wastewater rates (150% of the maximum water demand) in semiarid regions can raise the SOM (OLIVEIRA et al, 2016). The results of the present study showed an increase in SOM when compared to that before the experiment implementation (Table 1), presenting averages of 20.8% (0.0-0.2 m layer) and 28.6% (0.2-0.4 m layer); this can be explained by the decomposition of plant residues, such as leaves and stems of banana trees in the experimental area.…”
Section: Resultsmentioning
confidence: 99%
“…The observed high pH in August could have been due to the increase in temperature, which could have promoted higher rates of chemical reactions in water (Barron et al, 2006). In contrast the high values of pH could be beneficial in soils experiencing low pH, as it affects mobility of nutrients (Oliveira et al, 2016). Normally, the safe pH range in water is 6.5 to 8.4 (Jeong et al, 2016), but this could vary according to soil type.…”
Section: Discussion Ph and Electrical Conductivitymentioning
confidence: 99%
“…Similar results regarding the accumulation of magnesium in the soil due to the use of wastewater were also observed by Bourazanis et al (2016), when they tested the application of domestic effluents in the hydraulic conductivity of the soil and by Abegunrin et al (2016), when they evaluated the use of different types of effluents in the chemical and physical properties of the soil in relation to the water supply, both concluded that the domestic effluent can be an alternative of Mg to the soil. On the other hand, opposing these results and working with Cucurbita maxima Duch, irrigated with wastewater, Oliveira et al (2016) verified a reduction of Mg levels in the soil. Thus, it can be concluded that the nutrient intake of the wastewater varies for each condition and it is necessary to pay attention to the requirement of the crop.…”
Section: /7mentioning
confidence: 94%